Perlindungan Hukum Driver Gofood terhadap Pembatalan Pesanan Oleh Konsumen dengan Metode Cash On Delivery - Obbie Alexander Kusumo; Kadek Wiwik Indrayanti; Galih Puji Mulyono; Khotbatul Laila (University of Merdeka Malang, 2023)
The development of technology for implementing E-Commerce where Gojek as a Food Delivery Service Provider Application through its partners, namely drivers, problems often arise related to canceling food orders by consumers in the Cash On Delivery (COD) payment method in E-commerce transactions. This study contains a formulation of the problem regarding legal protection for gojek drivers against canceling food orders by consumers with the cash on delivery payment method. Based on the results of research on the legal protection of Gojek drivers against canceling food orders by consumers with the Cash On Delivery payment method where food orders have entered the merchant, payments to restaurants will be deducted from the Gojek balance or payments in cash directly by drivers to merchants. then that is where the end point of the limit for canceling orders by consumers which, if done, will result in default and Article 1243 of the Civil Code applies. So to protect the rights of drivers for canceling food orders by consumers with the cash on delivery payment method and based on the article above, drivers can file civil lawsuits against consumers who have defaulted.